Ultrasonic control of marine fouling - Yeo, Aziel Jie Kai (2017)
Biofouling is the natural attachment of organisms to a surface submerged in water, accumulating over time to form heavy and gregarious layers of coating. This poses as a major problem to the maritime industry, especially in the field of marine transportation. Accumulations of marine biofouling layers on the hulls of ships result in increased drag, significantly impacting the speed, fuel efficiency, range and manoeuvrability of marine vessels. The US Navy estimates the cost of fuel wastage due to marine biofouling to be $1.2 million per ship per year. Anti-fouling techniques to prevent the attachment or accumulation of fouling organisms, have been widely adopted to reduce the costs associated with biofouling. The most common of which are anti-fouling coatings that release biocides into the water. However, these biocides are not solely toxic to biofouling organisms, but are likewise harmful to larger marine organisms and to the environment in general. There has hence been a pressing need for more environmentally friendly anti-fouling solutions to be developed. In this project, the application of ultrasonic guided waves vibrating at 100 kHz in the shear horizontal mode was evaluated for effectiveness as a technique for marine fouling control. The degree of fouling on steel bars treated with the ultrasonic guided waves (treated bars) were compared against untreated control bars in 2 separate series of experiments. In the laboratory experiments, the bars were immersed in liquid cultures of Pseudomonas aeruginosa bacteria, whereas in the marine field experiments, the bars were submerged into the sea. The laboratory experiments yielded positive results in which the treated bars consistently exhibited lower levels of bacterial micro-fouling as compared to control bars. While the marine field experiments are still ongoing, promising results have already been observed, in which the treated bars 4 exhibited lower levels of marine biofouling than control bars. Both series of experiments hence support the hypothesis that ultrasonic guided waves vibrating in the shear horizontal mode is an effective application of ultrasound to achieve protection from marine biofouling. These experiments are early stages in the process of developing an environmentally-friendly and energy-efficient ultrasonic anti-fouling system utilizing shear horizontal guided waves.